RENTABILITAS BANK UMUM SYARIAH DI INDONESIA: STUDI DENGAN METODE VECTOR AUTOREGRESSIVE - Safarida, Nanda; Wirdaniah, Wirdaniah (HUMAN FALAH: Jurnal Ekonomi dan Bisnis Islam, 2023)
This study aims to determine the effect of operating costs and operating income, capital adequacy ratio, non-performing financing and inflation on the profitability ratio of Islamic commercial banks for the 2011-2020 period. This research method was used using time series data with VAR analysis, as well as data collection sourced from www.bi.go.id and www.bps.go.id site data for the period 2011-2020 with a total of 10 years of observations from all syarah commercial banks. The results showed that the BOPO variable had a positive and significant influence on the profitability ratio with a probability value of 0.03 < 0.05 the CAR variable has a positive and significant effect on the profitability ratio with a probability value of 0.02 < 0.05 the NPF variable has a positive and significant effect on the profitability ratio with a probability value of 0.01 < 0.05 the inflation variable has a positive and insignificant effect on the profitability ratio with a probability value of 0.38 > 0.05.